Lesões musculoesqueléticas em corredores e características do treinamento: descrições, associações e taxas de lesão - Hespanhol Junior, Luiz Carlos (2011)
There is no consensus in the literature about what are the main musculoskeletal injuries in runners. The objective of this study was to systematically review what are the main musculoskeletal running-related injuries (MRRI). Searches were conducted in the EMBASE, MEDLINE, SPORTDISCUS, LILACS and SCIELO databases, with no limit of publication date and language, conducted by March 2011. We considered eligible articles related with MRRI that describe the incidence or prevalence of each MRRI. We excluded studies that reported only the type of injury or anatomical region, studies with incomplete data and studies conducted with only injured runners. The data extracted of the articles were the following: first author, publication year, study design, description of the population of runners reported by article, MRRI definition and the MRRI with their respective rates of incidence or prevalence. From 2781 titles of articles found only eight were eligible for this review. Most articles had a good score in assessment of risk of bias. The main MRRI found were: patellar tendinopathy (incidence ranged from 5.5% to 22.7%; prevalence ranged from 6.3% to 18.5%), medial tibial stress syndrome (incidence ranged from 13.6% to 20.0%; prevalence ranged from 7.8% to 11.1%), Achilles tendinopathy (incidence ranged from 9.1% to 10.9%; prevalence ranged from 6.2% to 18.5%), plantar fasciitis (incidence ranged from 4.5% to 10.0%; prevalence ranged from 5.2% to 17.5%), patellofemoral syndrome (incidence ranged from 5.5% to 6.9%; prevalence ranged from 5.5% to 15.6%) and iliotibial band syndrome (incidence ranged from 1.8% to 9.1%; prevalence ranged from 4.7% to 10.5%). Therefore, the main MRRI found in this systematic review were: (1) patellar tendinopathy, (2) medial tibia stress syndrome, (3) Achilles tendinopathy, (4) plantar fasciitis, (5) patellofemoral syndrome, and (6) iliotibial band syndrome.